The Influence of The Role of Field Agricultural Extension Workers as Mediators on the Success of the Rice Farming Program - Sri Dewi Maharani; Ainun Sa'adah; Ibnu Aqiel; Mukhammad Khoirudzaki; Achmad Faqih (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Field agricultural extension workers are obliged to have learning concepts to support their role as mediators who will be a bridge in the process of diffusion, innovation, and problem solving in an organization. A mediator is expected to mediate what is needed by farmers and help overcome problems that arise and require appropriate solutions in handling them in the field. The objectives of this study are: 1) to determine the influence of the role of field agricultural extension workers as mediators in the availability of capital sources, study programs, technology dissemination, agro-industry, and simultaneous marketing of agricultural products on the success of the Rice Farming program. 2) knowing the influence of the role of field agricultural extension workers as mediators in the availability of capital sources, study programs, technology dissemination, agro-industry, and partial marketing of agricultural products on the success of the Rice Farming program. The research design used in this study is descriptive research with a quantitative approach. The population used is the Sri Mulya farmer group, Bodesari Village, Plumbon District, Cirebon Regency. The section examined is on the effect of the role of field agricultural extension workers as mediators on the success of rice farming programs. The number of samples used was 32 respondents. The study will be conducted in March - May 2023. Data analysis techniques use validity, reliability and regression tests. The results showed that: 1) the influence of the role of field agricultural extension workers as mediators simultaneously (availability of capital sources, study programs, technology dissemination, agro-industry, and marketing of agricultural products) affects the success of the rice farming program. 2) the influence of the role of field agricultural extension workers as partial mediators (availability of capital sources, study programs, technology dissemination, agro-industry, and marketing of agricultural products) on the success of the rice farming program